Lecanorchis moritae (Orchidaceae, Vanilloideae), a new mycoheterotrophic species from Amami-Oshima Island, Japan, based on morphological and molecular data - Suetsugu, Kenji; Kaida, Shingo; Hsu, Tian-Chuan; Sawa, Shinichiro (Phytotaxa, 2019)
A new species of the mycoheterotrophic genus Lecanorchis Blume (Orchidaceae), L. moritae, is described from Amami-Oshima Island, Japan. It is most similar to L. suginoana but differs in having a transversely elliptic (slightly contracted at base) midlobe (vs. semiorbicular, not contracted at base), more triangular with almost entire margins (vs. relatively rounded, denticulate margins) and reddish apices (vs. somewhat whitish apices) and a lip with white and purple hairs (vs. white and lemon yellow hairs) and sparse unicellular papillae scattered on the disc (vs. dense unicellular papillae). An illustration and nuclear ribosomal internal transcribed spacer (nrITS) sequence (i.e., DNA barcode) of the new species are also provided.